The incorporation of the Halal Management System (HMS) by the pharmaceutical industry - Ka-Liong Tan; Ainoon Othman; Irwan Mohd Subri; Noor Fadzilah Zulkifl i; Mohd Mahyeddin Mohd Salleh; Nazariyah Yahaya; Khairun Nain Nor Aripin; Shahirah Nadiah Shaharuddin; Seri Azalina Mohd Ghazalli; Muhammad Syazan Sulaiman (GABI, 2024)
Non-Indexed Publication